2017
DOI: 10.4111/icu.2017.58.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence rate of stress urinary incontinence in females with initial cure after transobturator tape procedure at 3-year follow-up

Abstract: PurposeTo assess recurrence rates of urinary incontinence in women with initial cure after transobturator tape (TOT) procedure at 3-year follow-up.Materials and MethodsBetween June 2006 and May 2013, a total of 402 consecutive patients underwent the TOT procedure for female stress urinary incontinence (SUI) at Dongguk University Ilsan Hospital. Of the 402 patients, 223 had sufficient medical records for analysis. Therefore, they were followed-up for 3 years postoperatively. Patient characteristics, urinary sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Although the difference between the two groups was small, the curative effect of the treatment group of pelvic floor reconstruction after TOT was better than that of the simple TOT group. Compared with other TOT operations reported in the literature, our surgery has a higher cure rate [ 13 ]. In the meta-analysis and evaluation of the short-term efficacy and adverse reactions of Ajust single incision micro urethral sling operation (Ajust operation) compared with standard middle urethral sling operation (TVT-O/TOT) by Wei et al, [ 14 ] 233 cases in TVT-O/TOT group were reported.…”
Section: Discussionmentioning
confidence: 88%
“…Although the difference between the two groups was small, the curative effect of the treatment group of pelvic floor reconstruction after TOT was better than that of the simple TOT group. Compared with other TOT operations reported in the literature, our surgery has a higher cure rate [ 13 ]. In the meta-analysis and evaluation of the short-term efficacy and adverse reactions of Ajust single incision micro urethral sling operation (Ajust operation) compared with standard middle urethral sling operation (TVT-O/TOT) by Wei et al, [ 14 ] 233 cases in TVT-O/TOT group were reported.…”
Section: Discussionmentioning
confidence: 88%
“…(32) En nuestro grupo de estudio el 2.9% necesito de dilataciones uretrales previa a la cateterización uretral continuo, solo un caso requirió movilización de la cinta dentro de las 2 semanas posteriores a la operación. (33) La exposición de malla tiene tasas de 0.8 a 5%, (10,11,27,34,35) y puede sobrevenir entre 3 semanas y 18 meses. (31) Vishwanath y su grupo reportaron extrusión de la cinta a las tres semanas de la intervención en 1 de 150 pacientes (1.5%), que era diabética y posmenopáusica y se trató con resección de la malla sin complicaciones.…”
Section: Discussionunclassified
“…Evidence on treatments for incontinence and prolapse from high income settings show that conservative management including pelvic floor muscle training can be effective, with studies showing cure being reported up to six times more for urinary incontinence vs. non-intervention ( 11 13 ). Surgical options are appropriate for women who have exhausted conservative management but are associated with high rates of reoccurrence ( 14 , 15 ). There is interest in whether similar models of conservative management would be appropriate and effective in lower-income country contexts.…”
Section: Introductionmentioning
confidence: 99%